Stem cell therapy in treatment of heart failure – a literature review - Zydlewski, Igor; Blecharczyk, Małgorzata; Jakubiec, Paweł; Kosiński, Maciej; Mrozek, Martyna; Nowik, Alicja; Pacanowska, Martyna; Sękulski, Marcin (Quality in Sport, 2025)
Introduction Heart failure is a condition defined as insufficient supply of oxygen to tissues, caused by a reduced cardiac output. It is usually associated with myocardial infarction or valve malfunction, but can also be a result of chronic diseases, such as hypertension or alcohol abuse. Despite the good state of knowledge about this disease and modern forms of treatment, heart failure remains a major therapeutic problem and a common cause of death around the world. The evolution of heart failure treatment over the years has revolved around managing the symptoms, yet failed to develop a causal treatment. Stem cell therapy has risen interest among researchers, as promising studies had emerged. The regenerative potential of stem cells and their paracrine properties are believed to improve cardiac function in patients with heart failure. Aim of study The aim of this study is to review randomized clinical trials published in the last 5 years and evaluate the safety and potential role of stem cell therapy in managing patients suffering from heart failure. State of knowledge Stem cells are capable of self-renewal and differentiating into other types of cells. They hold great promise in the field of regenerative medicine as a factor inducing tissue repair, reducing apoptosis and promoting angiogenesis. Animal studies have shown their positive effect on cardiac contractility and also reducing the amount of scar tissue, but subsequent studies in humans have not yielded consistent results. Conclusion Heart failure therapy using stem cells is a safe method. Promising results of clinical studies have been reported related to the improvement of contractile function of the heart, as well as reduction of scar mass and improvement of quality of life. However, there is still a lack of consistent data and guidelines regarding the selection of the type of cells and the method of their administration. This topic requires broader studies, on larger groups of patients.